Isolated liver gunshot injuries: nonoperative management is feasible? - STARLING,SIZENANDO VIEIRA (2015)
ABSTRACTObjective:to evaluate the safety and effectiveness of non-operative management (NOM) of liver injury, being the only abdominal injury, from gunshot wounds to the abdomen.Methods:patients who had liver damage diagnosed as single abdominal injury caused by PAF in the right thoracoabdominal region, hemodynamically stable were studied. All underwent examination with computed tomography. Were analyzed: age, gender, levels of trauma, hemodynamic condition and the abdominal examination on admission, the results of the CT scan, the extra-abdominal lesions found, the serum levels of hemoglobin, clinical course, complications, length of hospital stay, outpatient treatment and death.Results:during the study period 169 patients, treated non-operatively, presented liver gunshot wounds. Of these, only 28 patients (16.6%) had liver injury as the only abdominal injury and consequently met the inclusion criteria for this study. The average age was 27.7 years and 25 patients (89.2%) were male. The overall average of verified trauma scores were: RTS 7.45, ISS 10.9, and TRISS 98.7%. The most frequent injuries were grade II and grade III (85.7%). Complications occurred in only one patient who presented a progressive decline in hemoglobin. He underwent a CT scan which showed blush in the liver parenchyma. An arteriography was performed, which showed a successfully embolized arteriovenous fistula. There were no deaths in the patient sample. The average hospital stay was 5.3 days.Conclusion:isolated hepatic injury in gunshot abdominal trauma is uncommon. However, the NOM protocol for this type of injury is safe and has low morbidity. This approach should only be followed in institutions with adequate infrastructure, where an experienced and cohesive team is able to follow a specific protocol, with rigorous periodic evaluation of its results.